Understanding the adverse effects of salinity on lentil growth: Mechanisms and responses - Singh, Vijayata; Singh, Jogendra (Indian Farming, 2025)
Salinity is a major abiotic stress that significantly impairs lentil (Lens culinaris Medik.) growth, development, and productivity, especially in arid and semi-arid regions. This chapter provides a comprehensive overview of the physiological, biochemical, molecular, and agronomic responses of lentil to salinity stress. Salinity disrupts lentil growth at all stages- germination, vegetative, and reproductive- through osmotic stress, ion toxicity, and nutrient imbalances. Plants respond by accumulating osmoprotectants like proline and glycine betaine, activating antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD), and modifyingphotosynthetic and ionic regulation mechanisms. Advanced understanding of salt tolerance is facilitated by transcriptomics, proteomics, metabolomics, and ionomics, identifying stress-responsive genes, proteins, and metabolites. Breeding efforts involving wild relatives, marker-assisted selection (MAS), and genome-wide association studies (GWAS) are underway, complemented by transgenic and genome editing tools. Integration of high-throughput phenotyping and agronomic practices, such as seed priming and soil amendments, holds promise for developing salt-tolerant lentil varieties. The article underscores a multidisciplinary approach to enhance lentil resilience under salinity for sustainable pulse production.